Angiotensin (1–7) inhibits arecoline‐induced migration and collagen synthesis in human oral myofibroblasts via inhibiting NLRP3 inflammasome activation. Issue 4 (24th September 2018) - You, Yuehua; Huang, Yun; Wang, Dan; Li, Yang; Wang, Guozhen; Jin, Siyi; Zhu, Xintao; Wu, Bin; Du, Xinya; Li, Xu
Abstract: Arecoline induces oral submucous fibrosis (OSF) via promoting the reactive oxygen species (ROS). Angiotensin (1–7) (Ang‐(1–7)) protects against fibrosis by counteracting angiotensin II (Ang‐II) via the Mas receptor. However, the effects of Ang‐(1–7) on OSF remain unknown. NOD‐like receptors (NLRs) family pyrin domain containing 3 (NLRP3) inflammasome is identified as the novel mechanism of fibrosis. Whereas the effects of arecoline on NLRP3 inflammasome remain unclear. We aimed to explore the effect of Ang‐(1–7) on NLRP3 inflammasome in human oral myofibroblasts. In vivo, activation of NLRP3 inflammasomes with an increase of Ang‐II type 1 receptor (AT1R) protein level and ROS production in human oral fibrosis tissues. Ang‐(1–7) improved arecoline‐induced rats OSF, reduced protein levels of NADPH oxidase 4 (NOX4) and the NLRP3 inflammasome. In vitro, arecoline increased ROS along with upregulation of the angiotensin‐converting enzyme (ACE)/Ang‐II/AT1R axis and NLRP3 inflammasome/interleukin‐1β axis in human oral myofibroblasts, which were reduced by NOX4 inhibitor VAS2870, ROS scavenger N ‐acetylcysteine, and NOX4 small interfering RNA (siRNA). Furthermore, arecoline induced collagen synthesis or migration via the Smad or RhoA‐ROCK pathway respectively, which could be inhibited by NLRP3 siRNA or caspase‐1 blocker VX‐765. Ang‐(1–7) shifted the balance of RAS toward the ACE2/Ang‐(1–7)/Mas axis, inhibited arecoline‐induced ROS and NLRP3 inflammasome activation, leading to attenuation of migration or collagen synthesis. In summary, Ang‐(1–7) attenuates arecoline‐induced migration and collagen synthesis via inhibiting NLRP3 inflammasome in human oral myofibroblasts. Abstract : In this study, we deeply revealed that NLRP3 inflammasome triggered by arecoline‐induced ROS promotes OSF. Ang‐(1–7) attenuates migration and collagen synthesis in human oral myofibroblasts via inhibiting NLRP3 inflammasome.